The Effect of Distributed Generator Injection with Different Numbers of Units on Power Quality in the Electric Power System - Kurniawan, Robi; Nasution, Ardiansyah; Hasibuan, Arnawan; Isa, Muzamir; Gard, Muskan; Bhunte, Shrikant Vasantrao (Journal of Renewable Energy, Electrical, and Computer Engineering, 2021)
Distributed Generation (DG) is a small capacity generator located in the electricity distribution system and is usually placed on buses that are connected directly to the load. Placement of distributed generation is one of the technical efforts to reduce voltage drop and power losses in the system. In addition, load flow analysis is a study to plan and determine the amount of power in an electric power system. The results of power losses after adding distributed generation were the best in the fifth experiment on bus 149, where the system experienced a total loss of active power (P) previously of 720,822 kW, to 682,939 kW and total loss of reactive power (Q) previously of 530.02 kVar, to 405.835 kVar. From the results of the calculation of the power flow using ETAP software (Electrical Transient Analyzer Program). So, it can be concluded that the electrical network system can be said to be good. The results obtained are the more DG (wind turbine generator) that is input into the bus it will reduce the voltage drop that occurs. After simulating the overall voltage drop, it still meets the standards according to the results of the Text Report on ETAP.